Birth Intervals and Associated Factors among Women Attending Young Child Clinic in Yumbe Hospital, Uganda - Aleni, M.; Mbalinda, S. N.; Muhindo, R. (International Journal of Reproductive Medicine, 2020)
Introduction. Evidence suggests that both short and long birth intervals are associated with poor maternal and child health outcomes. However, current studies suggest that a number of births still occur at short intervals. The aim of this study was to document birth intervals and associated factors among women of reproductive age in rural Uganda. Materials and Methods. This was a cross-sectional study conducted among 296 women aged 15-49 years attending young child clinic at Yumbe Hospital who had at least two successive live births. Data was collected using interviewer-administered questionnaire. Birth interval was categorized according to the WHO-recommended birth interval of ≥24 months and <24 months. Results. Of the 296 participants, 86.6% desired a birth interval≥24 months with a desired median birth interval of 36 months. The actual median birth interval was 22 months. Slightly more than half of the women (52.4%) had short birth intervals. Factors which were likely to be associated with short birth intervals included being younger (15-24 years) (AOR=4.39, 95%CI=1.49‐12.93, P=0.007), not planning to have another pregnancy (AOR=0.33, 95%CI=0.18‐0.58, P=0.001), not deciding together with husband when to have the next child (AOR=3.10, 95%CI=1.53‐6.28, P=0.002), not always using contraceptives before the next pregnancy (AOR=0.28, 95%CI=0.12‐0.64, P=0.003), and lack of influence of husband on when to have the next child (AOR=2.59, 95%CI=1.44–4.64, P=0.001). Conclusion. Prevalence of short birth intervals is still high in rural Uganda (52.4%), although majority (86.6%) of the women desire optimal birth intervals. Factors which were likely to be associated with short birth intervals included young maternal age, not using contraceptives, and lack of male involvement in child spacing activities. Therefore, to optimize birth intervals, focused child spacing strategies targeting young women and men are needed.